Notes biological observations on some unrecorded epecies of phytophagous and predatory mites in Canary Islands - Pande, Y.D.=700 1 Carnero, A.; Hernandez, M.
(Es, En)
ilus., 7 ref.
Keywords: ACARINA; ACAROS NOCIVOS; CANARIAS; ESPAÑA